Consumers' perception towards takaful medical and health insurance plan / Nor'aini Ahmad - Ahmad, Nor'aini (2005)
Health insurance is necessary to obtain health care, yet coverage remains one of the most important factors in obtaining access to health services. People without health insurance are much more likely than insured person to go without needed care, including preventive services and regular care for chronic conditions and less likely to have a regular source of care. Health Insurance serves multiple constituencies and distinct purposes. It includes promoting health, obtaining health care for individual and families and protecting people financially from exceptional health care costs. The purpose of this study is to measure consumers' perception towards Medical and Health Insurance by Takaful Nasional. It is important to measure their perception and acceptance of this insurance plan.